2016
DOI: 10.1111/rda.12784
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endoscopic surgery for small animal reproduction

Abstract: Although endoscopic surgery entered its "golden era" in the mid-1980s, it is still advancing at a tremendous pace. Novel surgical techniques and devices are continuously developed and applied, and new indications (and/or contraindications) for the use of endoscopic surgery are routinely reported in the literature and subjected to systematic assessments. Although endoscopic surgery (laparoscopy in particular) has already become established as the gold standard in human medicine, it has yet to be proven as a via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This finding is consistent with prior survey‐based research, including studies from Jones et al published in 2017 and Enciso et al published in 2020, which identified that ovariectomy (OVE) and ovariohysterectomy (OHE) were the MIS procedures most performed by respondents 23,24 . This is likely a reflection of the earlier transition away from a traditional open celiotomy to MIS for OVE/OHE, and hence increased exposure to these procedures during training 25 . In addition, OVE and OHE require less specialized equipment and have a lower level of technical difficulty when compared with more advanced surgeries 8,26 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with prior survey‐based research, including studies from Jones et al published in 2017 and Enciso et al published in 2020, which identified that ovariectomy (OVE) and ovariohysterectomy (OHE) were the MIS procedures most performed by respondents 23,24 . This is likely a reflection of the earlier transition away from a traditional open celiotomy to MIS for OVE/OHE, and hence increased exposure to these procedures during training 25 . In addition, OVE and OHE require less specialized equipment and have a lower level of technical difficulty when compared with more advanced surgeries 8,26 .…”
Section: Discussionsupporting
confidence: 89%
“…23,24 This is likely a reflection of the earlier transition away from a traditional open celiotomy to MIS for OVE/OHE, and hence increased exposure to these procedures during training. 25 In addition, OVE and OHE require less specialized equipment and have a lower level of technical difficulty when compared with more advanced surgeries. 8,26 Surgeons and respondents alike had generally never performed most of the advanced laparoscopic and thoracoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%